Analytical method for fast screening and confirmation of multi-class veterinary drug residues in fish and shrimp by LC-MS/MS. Issue 3 (3rd March 2016) - Kim, Junghyun; Suh, Joon Hyuk; Cho, Hyun-Deok; Kang, Wonjae; Choi, Yong Seok; Han, Sang Beom
ABSTRACT: A multi-class, multi-residue analytical method based on LC-MS/MS detection was developed for the screening and confirmation of 28 veterinary drug and metabolite residues in flatfish, shrimp and eel. The chosen veterinary drugs are prohibited or unauthorised compounds in Korea, which were categorised into various chemical classes including nitroimidazoles, benzimidazoles, sulfones, quinolones, macrolides, phenothiazines, pyrethroids and others. To achieve fast and simultaneous extraction of various analytes, a simple and generic liquid extraction procedure using EDTA-ammonium acetate buffer and acetonitrile, without further clean-up steps, was applied to sample preparation. The final extracts were analysed by ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS). The method was validated for each compound in each matrix at three different concentrations (5, 10 and 20 ng g –1 ) in accordance with Codex guidelines (CAC/GL 71-2009). For most compounds, the recoveries were in the range of 60–110%, and precision, expressed as the relative standard deviation (RSD), was in the range of 5–15%. The detection capabilities (CCβs) were below or equal to 5 ng g –1, which indicates that the developed method is sufficient to detect illegal fishery products containing the target compounds above the residue limit (10 ng g –1 ) of the new regulatory system (Positive List System – PLS).